Validation of Short-Term and Ultra-Short-Term Heart Rate Variability Measurement Based on Photoplethysmogram Using Commercial Mobile Application (Journal of Medical Device Technology, 2024)
Heart rate variability (HRV) is a valuable tool for assessing autonomic function and diagnosing cardiovascular diseases. Electrocardiography (ECG) is considered the gold standard for HRV measurements. Photoplethysmography (PPG), a simpler and more convenient method has emerged as an alternative to ECG for HRV measurement. As a result of this technique, many mobile applications have been developed that claim to perform real-time HRV in short periods ranging from 10 seconds to 1 minute. However, HRV requires at least 5-mintues for accurate measurements. Therefore, this study aims to investigate the validity of short-term (5 min) and ultra-short-term ( 0.7) at a minimum duration of 0.5-minute, while SDNN required 1 minute. FA features (VLF, LF, LFnu, HFnu) required a minimum duration of 2 minute, while (HF, LF/HF, TP) required 3 minutes. In conclusion, Camera HRV app is suggested to be a valid surrogate to traditional PPG sensors and has the potential to be used in various fields.
Keywords: HRV; PPG; Ultra-short-term; Short-term; Camera Heart Rate Variability; Shimmer3 GSR+